Disruptive human resource management proceedings of the 1st International Conference (ICDHRM 2024), Bhubaneswar, India, 13-14 January 2024 - Patnaik, Srikanta 1967- (IOS Press, 2024)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- Human Capital with Technical Space -- Positive Guidance of College Students' Career Planning Values Combined with Computer Data Simulation Analysis -- Age-Appropriate Web Design for People over 60 Years Old with Cognitive Difficulties -- Construction of Educational Information Platform Based on Big Data -- Research on Innovative Ways of Talent Training Mode Combining Computer-Aided Teaching with Student Management -- Research on Automatic Matching and Learning of Technical Terms in English Translation Based on Semi-Supervised Learning -- Research on the Application of Translation Technology Combined with Computer in English Teaching -- Analyzing the Linkages Between Agricultural Modernization and Rural Residents' Livelihoods: A Case Study of China -- Neural Network-Based Performance Analysis Method for Engineering Management -- A BP Algorithm for Human Resource Management Turnover and Salary Forecasting -- Design of Human Resource Performance Appraisal System Integrating Big Data Technology -- Research on the Application of Data Mining Algorithm in the Optimal Decision of Enterprise Human Resource Planning -- Application of Competency Model in Enterprise Human Resource Recruitment Management -- Optimization of University Scientific Research Project Management Resources Based on Genetic Algorithm -- Simulation of Enterprise Human Resource Management Model Based on Long Short-Term Memory (LSTM) -- Optimization Method for Human Resource Decision Based on Hadoop Big Data Platform -- Hybrid Mechanism of Deep Q-Network (DQN) and Graph Mining Algorithm in "Six-Dimensional Integrated" Mental Health Assessment and Prediction: Taking Hefei University of Economics as an Example -- Design and Implementation of a GIS-Based Historical Catering Culture Evolution System.
Keywords: Konferenzschrift